AmpC β-Lactamases in Enterobacteriaceae - A Mini Review: Life Sciences-Microbiology - D, Bindu; Saikumar, Chitralekha (International Journal of Life Science and Pharma Research, 2023)
Beta-lactamases are enzymes that confer resistance to β-lactam antibiotics. Both Gram-positive and Gram-negative bacteria produces these enzymes. There are about 3000 enzymes that initially emerged from bacteria found in the environment to protect themselves from the natural β-lactam. After the 1980s, many transmissible enzymes were detected periodically, resistant to cephalosporins, monobactam, and carbapenems. These enzymes were classified based on function and molecular structure. Among them AmpC β-lactamases were found to be resistant to β-lactams and β-lactamases inhibitors. They are class C cephalosporinases that confer resistance to the first, second, third generation cephalosporins and cephamycin, and also resistance to beta-lactamases inhibitors such as sulbactam, tazobactam, and clavulanic acid. Family Enterobacteriaceae comprises many organisms that cause community and nosocomial infections, such as Escherichia coli, Klebsiella pneumoniae, Citrobacter spp, Enterobacter aerogenes, and Salmonella species. Beta-lactamases are produced by Enterobacteriaceae, where AmpC beta-lactamases are found to be one of the mechanisms. Different types of AmpC beta-lactamases: mutation/attenuation in the chromosome, induced plasmid-mediated AmpC beta-lactamases. Some Enterobacteriaceae, like Enterobacter, carry it on their chromosome, and some other Enterobacteriaceae has plasmid-mediated AmpC beta-lactamases. This type of resistance has led to increased mortality and morbidity. It is challenging to detect these AmpC beta-lactamases in diagnostic settings. Still, the detection of AmpC β- lactamases is cumbersome, and no approved methods are found in CLSI guidelines. But the prevalence of AmpC beta-lactamases has increased drastically in Asia. The review aims to give an overview of AmpC β-lactamases. The objective of this review is to review the evolution, types, detection methods, recent world epidemiology, treatment options, and current updates of the AmpC beta-lactamases.